Socioeconomic competence of local self-government bodies of largest cities - T. A. Frolova (Правоприменение, 2022)
The subject of the article is legal issues of municipal authorities’ activities in the field of socioeconomic development.The purpose of the article is to identify trends in the legal regulation of socioeconomic issues of organizing local self-government in the largest cities of the Russian Federation. The methodology includes formal legal interpretation of Russian legislative acts, decisions of Russian Constitutional Court as well as systemic analysis of municipal acts.The main results, scope of application. The article analyzes the division of powers between regional and municipal authorities. At the present stage of development of Russian federalism, a rather complex and unstable model of delimitation of powers between levels of public authority has developed, which does not contribute to the socio-economic development of municipalities. distribution of powers between levels of public authority. The question of the delimitation of powers acquires new content in the formation of urban districts with intracity division and intracity districts in the largest cities. Based on the experience of organization and activities of urban districts with intracity division of Chelyabinsk and Samara, the problems and prospects of this approach to territorial planning and the distribution of powers between levels of public authority are outlined. Special attention is paid to the problem of finding a balance between centralization and decentralization of local self-government. In this aspect, the issue of a more effective delimitation of powers between different levels of public authority comes to the fore in order to maintain a unified urban policy in the field of ensuring the socio-economic development of the largest cities of the Russian Federation.Conclusions. A comprehensive approach is needed to delineate powers between levels of public authority, taking into account the importance of the largest cities in the spatial development of the Russian economy and their role in the formation of urban agglomerations. Only centralized administration makes it possible to develop a unified urban infrastructure. Therefore, improving the interaction of public authorities and local self-government is a necessary condition and the most important area of work in major cities that requires joint efforts. However, at the same time, it is necessary to avoid the degeneration of local self-government into a state one and the loss of the internal content of this institution of public power.